1987
DOI: 10.1007/bf01412216
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle-X-ray scattering by crystalline polymer fibres 1. Experimental method and investigation of the linear paracrystalline model

Abstract: Hosemann's formula for X-ray scattering by a linear paracrystal is investigated using the distribution of intensity parallel to the fibre axis of oriented poly(butylene terephthalate). The formula was put into a form suitable for numerical analysis, and a stepping refinement procedure used to adjust the paracrystalline parameters so that the discrepancy between the calculated and measured intensity was minimised. The measured intensity had been corrected for the spread of scattering transverse to the fibre axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Since the previous investigation [4] had shown that good agreement with experimental data was obtained for a model in which both crystalline and amorphous phase lengths were distributed according to the Reinhold [5] where y is a parameter controlling both the skew and the dispersion of the distribution, e = (Y> (1 -2 y r), and < Y> is the mean length. Provided 0 < y < 0.5, lengths less than e are not possible, since this would cause h(Y) to be negative.…”
Section: Determination Of Model Parametersmentioning
confidence: 89%
See 3 more Smart Citations
“…Since the previous investigation [4] had shown that good agreement with experimental data was obtained for a model in which both crystalline and amorphous phase lengths were distributed according to the Reinhold [5] where y is a parameter controlling both the skew and the dispersion of the distribution, e = (Y> (1 -2 y r), and < Y> is the mean length. Provided 0 < y < 0.5, lengths less than e are not possible, since this would cause h(Y) to be negative.…”
Section: Determination Of Model Parametersmentioning
confidence: 89%
“…More recently, Hall et al [4] have developed experimental techniques of recording the intensity distribution at a resolution sufficient to avoid distortion by instrumental effects. These use a linear position sensitive detector (LPSD) enabling the statistical uncertainty of the data to be determined, and Eq.…”
Section: -Hglz U'mentioning
confidence: 99%
See 2 more Smart Citations
“…number-average and weight-average molar weights, M n and M w ; crystal weight fraction, X c ; most probable crystal thickness, L c ; thickness distribution parameter, γ; number of coherently scattering lamellae, N relevant equations for computing the SAXS intensity profiles have been already reported by several authors [22,23]. The disorder parameters were assessed from the best fitting of the model with experimental data, taking the L c and L a values as determined above, and assuming γ c = γ a = γ.…”
Section: Experimental Methodsmentioning
confidence: 99%